A metabolomics and proteomics study of the Lactobacillus plantarum in the grass carp fermentation - Tinghong Ming; Jiaojiao Han; Yanyan Li; Chenyang Lu; Dihong Qiu; Ye Li; Jun Zhou; Xiurong Su (BMC Microbiology, 2018)
Abstract Background Lactobacillus plantarum, a versatile lactic acid-fermenting bacterium, isolated from the traditional pickles in Ningbo of China, was chosen for grass carp fermentation, which could also improve the flavor of grass carp. We here explored the central metabolic pathways of L. plantarum by using metabolomic approach, and further proved the potential for metabolomics combined with proteomics approaches for the basic research on the changes of metabolites and the corresponding fermentation mechanism of L. plantarum fermentation. Results This study provides a cellular material footprinting of more than 77 metabolites and 27 proteins in L. plantarum during the grass carp fermentation. Compared to control group, cells displayed higher levels of proteins associated with glycolysis and nucleotide synthesis, whereas increased levels of serine, ornithine, aspartic acid, 2-piperidinecarboxylic acid, and fumarate, along with decreased levels of alanine, glycine, threonine, tryptophan, and lysine. Conclusions Our results may provide a deeper understanding of L. plantarum fermentation mechanism based on metabolomics and proteomic analysis and facilitate future investigations into the characterization of L. plantarum during the grass carp fermentation.